Pengaruh Variasi Dosis Pupuk Kasgot Kotoran Ayam Terhadap Pertumbuhan Tanaman Cabai Merah Besar (Capsicum annuum L.) - Puji Setiyo Rini; Fita Fitriatul Wahidah (Flora : Jurnal Kajian Ilmu Pertanian dan Perkebunan, 2024)
Chili is one of the superior horticultural products which has quite high economic value. The demand for large red chili supplies is causes farmers to plant chilies continuously without paying attention to environmental factors. The use of kasgot fertilizer in the cultivation process can have a positive impact on plants. This research aimed to determine the effect of doses variants for the growth of Capsicum annuum L. The research method used RAL with 6 treatments K1: 150g. K2: 175g, K3: 200g, K4: 225g, K5: 250g, and K6: 275g each treatment was repeated 4 times to obtain 24 samples. Observation parameters include plant height, number of leaves, number of fruit and fruit weight. Data analysis used One Way ANOVA and continued with the Tukey test. Varying doses of kasgot fertilizer have a real influence on the growth parameters of plant height, number of leaves, number of fruit and fruit weight. Treatment with a dose of kasgot fertilizer (K1) 150g gave the highest average number of fruit (10.3 pieces) and fruit weight (82.375g). Meanwhile, a dose of 175g (K2) gave the highest average plant height (37.5 cm) and number of leaves (50.45 each). So the optimal dosage of kasgot fertilizer for the growth of large red chili plants is around 150-175g.